If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 2(-1x + 3) Reorder the terms: 24 = 2(3 + -1x) 24 = (3 * 2 + -1x * 2) 24 = (6 + -2x) Solving 24 = 6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 24 + 2x = 6 + -2x + 2x Combine like terms: -2x + 2x = 0 24 + 2x = 6 + 0 24 + 2x = 6 Add '-24' to each side of the equation. 24 + -24 + 2x = 6 + -24 Combine like terms: 24 + -24 = 0 0 + 2x = 6 + -24 2x = 6 + -24 Combine like terms: 6 + -24 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| 2(3y+4+2)= | | 17+10x-3=-3(x-6) | | 14x+8+10x+28=180 | | 9x+5=12x-19 | | 6-(-7+x)=42 | | 600=2x+3y | | -6(5n+5)=-120 | | 8x-27=4x+33 | | 140=90+m | | 12-4x=-5x+22 | | 12x^2+26x-10=0 | | 2(g+4)+5g-1= | | 3n+28=200 | | 0.75n+1.29=7.00 | | x(2x-5)(x^2-3)(5x^3-8)=0 | | -3x=-5x+22 | | 5x-31=2x+5 | | 7x-36=4x+5 | | 5y-[2(y+1)+2]=7z | | (4.6-8n)0.5=3.8 | | 4n-25=75 | | 2(4-x)+7x=13 | | 4x+4=7x-17 | | x+5.5y=x+y+81 | | 4(5a+16)=16(a-35) | | 3x^4-13x^2=10 | | 32n+120=720 | | 6x-29+2x+24=67 | | 4(1+8v)+5v=-255 | | 8y+25=4y-27 | | 4(1+8)+5v=-255 | | 2x-9-5x=17-3x-42+8x |